1971
DOI: 10.1017/s0043174500049286
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Johnsongrass Selections Under Different Temperatures and Dark Periods

Abstract: The differential response of three selections of johnsongrass (Sorghum halepense(L.) Pers.) to different temperatures and dark periods was studied in two experiments conducted in growth chambers. The three selections of johnsongrass were obtained from locations representing different climates. At 20 C all three selections grew equally with respect to most parameters of growth studied; however, at 35 C the selection from the southern climate produced more total fresh weight than the other two selections. Rhizom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1
2

Year Published

1974
1974
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
3
15
1
2
Order By: Relevance
“…It was found that seed germination at 20°C was less than 10% for forty-three Johnson grass ecotypes and between 10% and 20% for one ecotype (Taylorson & McWhorter, 1969), With alternating tempera-Sorghum halepense 263 tures, twenty-three ecotypes had less than 10% germination, another twenty-one had more than 10%, one ecotype having 50-^0% germination. Control 5 weeks after dalapon application at 11 kg/ha varied from 36% for a Louisiana selection to 91% for a Georgia selection (McWhorter & Jordan, 1976b), The number of tillers produced by different ecotypes after a 14 week period varied from 7 to 12 (Wedderspoon & Burt, 1974), Production of rhizome nodes varied from 94 to 229 in 10 weeks (McWhorter & Jordan, 1976b), Burt & Wedderspoon (1971) showed ecotypic variation in flowering response to photoperiod, Spikelet production varied from 37 to 352 sessile spikelets per panicle and the incidence of shattering varied from 1 to 73% for sixteen American ecotypes (McWhorter, 1971), The same author reported that Johnson grass plants from Turkey, Ethiopia and the Dominican Republic did not overwinter in Mississippi unlike American, Indian, Pakistani, Iranian and Israeli ecotypes.…”
Section: Life Eycle and Variabilitymentioning
confidence: 99%
“…It was found that seed germination at 20°C was less than 10% for forty-three Johnson grass ecotypes and between 10% and 20% for one ecotype (Taylorson & McWhorter, 1969), With alternating tempera-Sorghum halepense 263 tures, twenty-three ecotypes had less than 10% germination, another twenty-one had more than 10%, one ecotype having 50-^0% germination. Control 5 weeks after dalapon application at 11 kg/ha varied from 36% for a Louisiana selection to 91% for a Georgia selection (McWhorter & Jordan, 1976b), The number of tillers produced by different ecotypes after a 14 week period varied from 7 to 12 (Wedderspoon & Burt, 1974), Production of rhizome nodes varied from 94 to 229 in 10 weeks (McWhorter & Jordan, 1976b), Burt & Wedderspoon (1971) showed ecotypic variation in flowering response to photoperiod, Spikelet production varied from 37 to 352 sessile spikelets per panicle and the incidence of shattering varied from 1 to 73% for sixteen American ecotypes (McWhorter, 1971), The same author reported that Johnson grass plants from Turkey, Ethiopia and the Dominican Republic did not overwinter in Mississippi unlike American, Indian, Pakistani, Iranian and Israeli ecotypes.…”
Section: Life Eycle and Variabilitymentioning
confidence: 99%
“…Observations in the greenhouse and field indicate that glyphosate phytotoxicity may be influenced by several application and environmental factors. Environmental variables such as soil moisture, air temperature, stage of plant growth, light, and relative humidity have been shown to affect the performance of foliar-applied herbicides (1,2,5,7,10,12,13). The addition of surfactants (11,18) and other additives such as inorganic salts (15,16) and carrier volume (11,15,16) also influences glyphosate phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Depth of rhizome production in the field and tolerance to cold is not known for populations of this species at the northern extreme of its distribution in North America. Considerable intraspecific variability has been described for populations of S. halepense throughout its range, and this variability has been suggested as important for the rapid adaptability of this species to more northern climates (Burt & Wedderspoon, 1971). It was, therefore, of considerable interest to compare winter survival parameters in the two contrasting biotypes of 5".…”
mentioning
confidence: 99%